A importância das atividades intelligence da contabilidade de gestão para as estratégias e políticas comerciais nas PME´s Portuguesas - Santos, Célia da Conceição da Rocha (2022)
Methodology – This study uses a quantitative approach, in the form of a questionnaire, using the statistical programs: SPSS 26 and AMOS 20. The empirical study is divided into two parts. The first part of the study uses the analysis of structural equations and the second part of the study is elaborated using the measures of central tendency (mean, median and mode) and the paired t-test to give more robustness to the results. Findings – The main result obtained with the realization of this study consists in the validation of a conceptual model where it is revealed that the intelligence activities of management accounting have positive effects on the commercial strategies and policies of Portuguese Small and Medium Enterprises. And, commercial strategies and policies have positive effects on the financial and non-financial performance of Portuguese Small and Medium Enterprises. Original value – Presentation of an original conceptual model that reveals the importance of management accounting in the definition of business strategy in Portuguese Small and Medium Enterprises.